Penerapan Metode GOMS untuk Evaluasi Perangkat Lunak Pemodelan Visual Berbasis Open Source - Harijanto Pangestu (Bina Nusantara University, 2012)
Software evaluation is needed to determine the usability level of the software. Good usability is having the following characteristics: effective to use (effectiveness), efficient to use (efficiency), safe to use (safety), having good utility (utility), easy to learn (learnability) and easy to remember how to use (memorability). Analytical evaluation is one evaluation approach that does not involve users. The evaluation is conducted by experts associated with the product. One method used in the analytical evaluation is GOMS, a method to analyze a task related to human computer interaction. GOMS does not provide accurate calculation of how users interact with the system, yet it estimates the time need to do a task dealing with the system. With the evaluation of UML users are expected to be able to use UML tools that appropriate to particular needs based on open source.